Влияние нарушение функции селезенки на жизнедеятельности организма. Изменение состояние организма после разрыва селезенки - Сайдалиходжаева С.З; Султонова С.А; Ашуров С.Р. (Open Academia, 2024)
The spleen is involved in immune defense and blood filtration. Disturbances in its function lead to immunodeficiency and an increased risk of infections. A ruptured spleen causes massive blood loss and shock, requiring emergency treatment. Removal of the spleen (splenectomy) results in chronic immunodeficiency and the risk of severe infections, highlighting the importance of its functionality to the health of the body
Keywords: spleen; periarterial lymphoid sheaths; red pulp